Removal of Iron Oxide from Indoor Air at a Subway Station Using a Vegetation Biofilter: A Case Study of Seoul, Korea - Tae-Han Kim (MDPI AG, 2021)
Recently, metallic particulate pollutants floating underground have been reported to negatively affect the human body. Thus, there is an urgent need for a public health policy pertaining to the air quality in subway stations. In this study, we investigated whether a vegetation biofilter is effective in reducing metal particle contaminants, especially iron oxide. After selecting a subway station, a vegetation biofilter system was installed, and samples were collected three times, at three intake areas and one exhaust area. The average weight ratio of the detected elements was calculated. The iron oxide reduction effect was evaluated using the Wilcoxon signed rank test. In the return air, C, O, and Fe were detected at 64.9, 27.3, and 5.2 wt.%, respectively; in the supply air, C, O, and Fe were detected at 67.2, 30.4, and 0.7 wt.%, respectively. The difference in the average Fe weight ratio was statistically significant. Air quality has a considerable effect on human health. We confirmed the possibility of reducing Fe in particulate matter using biofilters. However, we could not confirm whether the air quality was improved enough to not have a negative effect on the human body. This should be elucidated through follow-up studies.